Discrete-time modelling for performance analysis and optimisation of uplink traffic in IEEE 802.16 networks. (1st January 2013) - Goswami, Veena; Misra, Chinmaya
This paper analyses the performance and optimisation of uplink traffic in IEEE 802.16 networks of the different service classes. IEEE 802.16 standard suite is currently the latest broadband wireless access reservation-based bandwidth allocation mechanism. An 802.16 wireless service provides a communications path between a subscriber station (SS) and a base station (BS) with uplink and downlink directions. A SS has to be polled to request bandwidth reservation before transmits uplink data to a BS with an appropriate QoS. A discrete-time Geo/G/1 queuing model is utilised to investigate the performance of uplink traffic in IEEE 802.16 networks using the imbedded Markov chain technique. Some performance measures and illustrative numerical results have also been discussed. A cost model is developed to determine the optimal values of arrival and service rate at a minimum cost. The genetic algorithm is employed to search the optimal values of arrival and service parameters for the system.